Financial and administrative constraints among principals of primary and secondary government schools affiliated to the Directorate of Education in Aqaba Governorate from their point of view - Al Osaily, Kholoud Mahmoud (Journal of Educational and Psychological Sciences, 2018)
The objective of the study was to identify the Financial and administrative constraints to the principals and principals of the basic and secondary schools of the State of the Directorate of Education in the Governorate of Aqaba. In order to achieve the objective of the study, the researcher used the descriptive approach, The study tool was in a questionnaire distributed to a sample of the study consisted of 71 managers representing 100% Of the study population. Of these, 19 were managers and 52 managers, Using the statistical program (Spss) The results of the study showed that the total degree of financial and administrative obstacles encountered by the principals and principals of the basic schools, as well as the number of school principals and principals, And secondary in the Directorate of Aqaba Governorate from their point of view, achieved an average level, with an average of (3.55) with a high degree . There are statistically significant differences between the financial constraints of school administration and the obstacles Exclusive for the benefit of administrative obstacles.